Experimental Study on Hydration Mechanism of Lime-Gypsum Fly Ash Cement Paste - Xu, Zifang; Yang, Zheng; Tang, Yongkang (Asian Journal of Chemistry, 2013)
This work is based on the study of the fly ash lime gypsum cement paste setting time, the hydration heat and the compressive strength, by using differential scanning calorimeter-thermal gravimetry, scanning electron microscope and X-ray diffraction to separately analysis effects of different blending proportion fly ash on the hydration properties of cement paste. The results show that the hydrating capacity of early age is weak, but long term is-lasting, an increase of fly ash replacement causes a longer setting time of cement-based materials, a decrease of hydration heat; when fly ash replacement is 40 %, compressive strength decrease evident. The main hydration products of early age of fly ash lime gypsum is a large quantity of calcium silicate hydrate gel (C-S-H), without hydrate calcium silicate, smack ettringite and calcium hydroxide. The main hydration products fill with the pore space and mutual cross linking, efficiency improve the fly ash cement paste strengths.